REKAYASA PERANGKAT LUNAK PRODUKSI PACKAGING DENGAN METODE MRP2 DAN ALGORITMA OPTIMASI GREEDY - Nasri, Edy; Usri, Andi; Surahmat, Ahmad (Teknik Informatika Fakultas Ilmu Komputer, 2018)
Production Software Engineering is a process in planning and controlling manufacturing systems when carrying out short and medium term operations in the process of making products in the industry. Preparation of scheduling and control of inaccurate production can lead to inefficient production processes resulting in high production of waste, and will cause idle stock which can lead to high production costs. Approach to integrated system Manufacturing Resource Planning (MRP2) is a formal manufacturing information system and explicit that integrates the main functions in the manufacturing industry. Production Software Engineering with the MRP2 Method can be implemented in the production process starting from MRP, Capacity Requirements Planning (CRP), and in the Production Control Activity (PCA). Application of greedy optimization algorithms in planning and controlling production will provide a better solution that can reduce waste products. Because order allocation in the selection of raw material specifications and arrangement of production machine lines with greedy optimization algorithms are carried out gradually starting from finding local to global solutions. Global solutions are obtained by passing the selection function to find all possible solutions, constraint functions to free the results of the selection function from existing constraints and objective functions to determine the objectives to be achieved, namely optimization on production planning and control. Implement planning methods in production that refers to the order of orders received, then placed on the order of the available production machines both in capacity and specifications in accordance with the order of the production machines without considering which order of machinery can obtain the most optimal results.